Analisis Korelasi Manajemen Inventory Terhadap Strategi Pemasaran dan Efisiensi Bisnis Grosir Zube RM - Imron Akbar; Yanto Zelibu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyse the effect of inventory management on marketing strategy and business efficiency at Grosir Zube RM, as well as to examine the role of marketing strategy as a mediating variable in this relationship. A quantitative approach was used in this study with the Partial Least Squares Structural Equation Modelling (PLS-SEM) method through the SmartPLS application. Data were collected through questionnaires with respondents who were part of the wholesale's operations and management. The results showed that inventory management had a significant and positive effect on marketing strategy (coefficient = 0.799; p-value = 0.000) and business efficiency (coefficient = 0.716; p-value = 0.000). Furthermore, marketing strategy also has a significant effect on business efficiency (coefficient = 0.499; p-value = 0.000). The indirect effect test indicates that marketing strategy significantly mediates the relationship between inventory management and business efficiency (coefficient = 0.399; p-value = 0.001). Thus, it can be concluded that successful inventory management not only has a direct impact on operational efficiency but also strengthens marketing strategy, which in turn improves overall business efficiency. These findings emphasise the importance of integrating logistics and marketing functions to improve wholesale business performance.